2017
DOI: 10.1002/mds.26920
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype‐ and genotype‐specific structural alterations in spasmodic dysphonia

Abstract: Background Spasmodic dysphonia is a focal dystonia characterized by involuntary spasms in the laryngeal muscles that occur selectively during speaking. Although hereditary trends have been reported in up to 16% of patients, the causative etiology of spasmodic dysphonia is unclear, and the influences of various phenotypes and genotypes on disorder pathophysiology are poorly understood. In this study, we examined structural alterations in cortical gray matter and white matter integrity in relationship to differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 43 publications
1
40
0
Order By: Relevance
“…These structures are known to contribute to the important aspects of speech comprehension, motor planning and coordination, articulatory modulations, and pitch and tone control during singing . Functional and structural alterations in the inferior frontal gyrus and anterior insula are in line with previous neuroimaging studies in SD, which identified abnormal relationships between inferior frontal volume and activity during symptomatic task production as well as between insular volume and the disorder severity . Furthermore, a spatial disorganization of anterior insular structural connectivity with the inferior frontal gyrus was recently demonstrated in SD patients compared to healthy individuals .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These structures are known to contribute to the important aspects of speech comprehension, motor planning and coordination, articulatory modulations, and pitch and tone control during singing . Functional and structural alterations in the inferior frontal gyrus and anterior insula are in line with previous neuroimaging studies in SD, which identified abnormal relationships between inferior frontal volume and activity during symptomatic task production as well as between insular volume and the disorder severity . Furthermore, a spatial disorganization of anterior insular structural connectivity with the inferior frontal gyrus was recently demonstrated in SD patients compared to healthy individuals .…”
Section: Discussionsupporting
confidence: 80%
“…12,[34][35][36][37][38][39][40][41] Functional and structural alterations in the inferior frontal gyrus and anterior insula are in line with previous neuroimaging studies in SD, which identified abnormal relationships between inferior frontal volume and activity during symptomatic task production as well as between insular volume and the disorder severity. 42,43 Furthermore, a spatial disorganization of anterior insular structural connectivity with the inferior frontal gyrus was recently demonstrated in SD patients compared to healthy individuals. 40 Given that the neural circuits responsible for the control of speaking and singing potentially overlap, 36 our findings suggest that these regional alterations, too, reflect a commonly affected voice-specialized modality across different forms of laryngeal dystonia.…”
Section: Discussionmentioning
confidence: 98%
“…Among these, primary sensorimotor changes tended to localize to dystonia-affected body regions within the sensorimotor homunculus. For example, gray matter volumetric increases in patients with focal hand dystonia were observed in the hand area of sensori-motor cortex (Delmaire et al, 2005; Egger et al, 2007; Garraux et al, 2004), whereas in patients with laryngeal dystonia these were found within the larynx representation (Bianchi et al, 2017; Kostic et al, 2016; Simonyan & Ludlow, 2012), further showing relevance of cortical aberrations to the pathophysiology of distinct forms of dystonia.…”
Section: Structural Neuroimaging Of Dystoniamentioning
confidence: 99%
“…As gene discovery for isolated focal dystonias remains stagnant and extremely challenging due, in part, to rare availability of large families, low penetrance, and variable expressivity, the design of neuroimaging studies has also been limited by somewhat arbitrary assignments of experimental cohorts based on a confirmed family history of dystonia only. Based on such approach, one recent study in patients with sporadic and familial forms of laryngeal dystonia identified phenotype-specific gray matter abnormalities in primary and associative areas of motor control that were distinct from genotype-specific changes within the cortical regions controlling sensory processing (Bianchi et al, 2017) (Fig. 2C).…”
Section: Structural Neuroimaging Of Dystoniamentioning
confidence: 99%
See 1 more Smart Citation